Preparation of Au/silica/poly(ethylene glycol) nanoparticle colloid solution and its use in x-ray imaging process. Issue 2 (29th April 2015) - Kobayashi, Yoshio; Nagasu, Ryoko; Nakagawa, Tomohiko; Kubota, Yohsuke; Gonda, Kohsuke; Ohuchi, Noriaki
Abstract: In this work, the authors performed X-ray imaging of mice using a colloid solution of Au nanoparticles that are coated with silica and subsequently surface-modified with poly(ethylene glycol) (PEG) (Au/SiO2 /PEG). The silica-coating for Au nanoparticles and the amination for silica-coated particles were simultaneously performed in the presence of the Au nanoparticles, which were prepared by reducing Au ions (III) with sodium citrate in water at 80°C and by surface-modifying the Au nanoparticles with (3-aminopropyl)-trimethoxysilane (APMS), by a sol–gel process using tetraethylorthosilicate (TEOS), (3-aminopropyl)-triethoxysilane, water and sodium hydroxide (Au/SiO2 -NH2 ). The surface modification of Au/SiO2 -NH2 particles with PEG was performed by simply adding PEG with a functional group that reacts with an amino group to the Au/SiO2 -NH2 particle colloid solution. A computed tomography value of the Au/SiO2 /PEG colloid solution with an Au concentration of 0.129M was as high as 895 ± 8 HU. Mouse tissues were imaged following injection of the Au/SiO2 /PEG particle colloid solution. Abstract :